P‐71: Encoding Saliency Information in Video Sequences and Its Application to Backlight Scaling of High Dynamic Range (HDR) LCDs. Issue 1 (May 2016) - Park, Jae Sung; Lee, Dae-Hyun; Hwang, Insung; Cho, Nam Ik
Abstract : This paper presents a framework that encodes saliency information in a video sequence at the encoder and uses this information for backlight scaling at the decoder. The saliency region in a scene is extracted and encoded as a supplementary information of H.264/AVC codec in our scheme. The saliency information decoded at the receiver is used to highlight the saliencies in the scene, which enhances the dynamic range of output images.